Strategic Cosmopolitanism: Chinese Female Jadeite Live Streamers in Ruili - Mingyue Yang; Ching Lin Pang (Cosmopolitan Civil Societies: An Interdisciplinary Journal, 2024)
With China's construction of free trade zones and the development of digital technology, immigrants from Myanmar and internal migrants from all parts of China have gathered in Ruili, a cross-border hub connecting the two countries. As a result of these mobilities it has been transformed into a grass-roots level cosmopolitan area. Through six years of fieldwork, this study found that grassroots female live streamers who were excluded from mainstream metropolises gained more opportunities for survival and development in jadeite cross-border trade activities in Ruili through the concepts of female entrepreneurship and everyday strategic cosmopolitanism The notion of strategic cosmopolitanism refers to non-elite openness as a strategic response to economic, employment or career advancements generated by policies, discursively presented as economic cosmopolitanism. The increase in economic gains for some has significantly improved their socio-economic status, while at the same time paying the price of being locked in the logic and rules of capitalism.